2023
DOI: 10.1186/s12866-023-02870-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed Lacticaseibacillus paracasei GMNL-653 ameliorates human scalp health by regulating scalp microbiome

Abstract: Background The equilibrium of the scalp microbiome is important for maintaining healthy scalp conditions, including sebum secretion, dandruff, and hair growth. Many different strategies to improve scalp health have been reported; however, the effect of postbiotics, such as heat-killed probiotics, on scalp health remains unclear. We examined the beneficial effects of heat-killed probiotics consisting of Lacticaseibacillus paracasei, GMNL-653, on scalp health. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…For scaling and cleaning perception, these parameters were suppressed by ST11 strain after 4 weeks [ 56 ], while B. lactis exhibited potential benefits only for scaling after 4 weeks [ 57 ]. Tsai's 2023 study [ 49 ] found decreased dandruff and oil secretion and increased hair growth with a heat-killed L. paracasei -containing shampoo.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For scaling and cleaning perception, these parameters were suppressed by ST11 strain after 4 weeks [ 56 ], while B. lactis exhibited potential benefits only for scaling after 4 weeks [ 57 ]. Tsai's 2023 study [ 49 ] found decreased dandruff and oil secretion and increased hair growth with a heat-killed L. paracasei -containing shampoo.…”
Section: Resultsmentioning
confidence: 99%
“… Baek 2022, Korea [ 62 ] HDPCs cell Topically treated shaved 6-week-old C57BL/6 mice (5 groups/each group 3 subjects) HDPC proliferation Histological evaluation: skin thickness mRNA hair growth gene expression: - FGF2, FGF7, FGF10 - Wnt5a, Wnt5b, Wnt10b - VEGF A, VEGF B, IGF-1, IGF1-R G1: Control (PBS) G2: 5 % minoxidil G3: 0 mg/mL EF-2001 in acetone + olive oil (3:1) G4: 5 mg/mL EF-2001 G5: 50 mg/mL EF-2001 E. faecalis EF -2001 accelerated the progression of hair regrowth in mice and promoted hair-follicle conversion from telogen to anagen, likely by increasing the expression levels of growth factors (VEGF A, VEGF B, IGF-1, IGF1-R, FGF2, FGF7, FGF10) and marker genes (Wnt5a, Wnt5b, Wnt10b) after 14 days Lee 2022, Korea [ 61 ] HFDPC cell NIH3T3 cell Orally treated shaved 7-week-old C57BL/6 mice (5 groups/each group 6 subjects) HFDPC proliferation Histological evaluation: Hair follicles, skin thickness mRNA hair growth gene expression: VEGF, IGF-1 G1: Negative control G2: Medicinal yeast (200 mg/kg) G3: Lycopus lucidus – LT (100 mg/kg) G4: L. paracasei HY7015 (10 8 CFU) G5: LT + HY7015 (100 mg/kg) Oral administration of G5 promoted hair regrowth as well as hair follicle maturation in the dermal skin of C57BL/6 mice and upregulated VEGF and IGF-1 growth factor levels in mouse serum in 5 weeks Yoon 2022, Korea [ 64 ] HFDPCs cell HFDP Cell Migration and Proliferations mRNA Cisplatin-Induced HFDP Cells gene expression: CCK-8, Bcl-2, Bax, Capcase-3 mRNA hair growth gene expression: Wnt5a, Wnt10b, b-catenin, versican (VCAN), VSC, BAMBI, BMP-2, Lef1 Apoptosis and Induce Division via Control Cell Cycle in HFDP Cells G1: Control G2: Bifidobacterium longum (Bl) G3: B . animalis G4: L. acidophilus G5 : human-scalp-derived- Leuconostoc holzapfelii (hs-Lh) G6: L. plantarum (Lp) G5 (10 10 particles) extracellular vesicles increase cell proliferation, and migration, and regulate the cell cycle G5 modulates the mRNA expression of hair-growth-related genes in vitro , reduces apoptosis by modulating the cell cycle, and promotes hair growth by regulation via the Wnt/β-catenin signal transduction pathway Tsai 2023, Taiwan [ 49 ] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations